Microimaging Characterization of a B16-F10 Melanoma Metastasis Mouse Model - Christopher T. Winkelmann; Said Daibes Figueroa; Tammy L. Rold; Wynn A. Volkert; Timothy J. Hoffman (Molecular Imaging)
Metastatic mouse models of melanoma have been characterized by gross necropsy examination, histopathology, and optical imaging. To determine if the time progression, extent, and metabolism of melanoma metastases could be monitored noninvasively, serial micro-CT and small-animal PET imaging studies were performed by using a mouse model of melanoma. Juvenile female C57BL/6 mice were injected intravenously with syngenic B16-F10 melanoma cells. Serial micro-CT imaging studies were performed on anesthetized mice. Mice were necropsied at the development of adverse clinical signs or at postinjection Day 30, and tissues were collected for histopathology. In a separate study of four mice, tumor viability was assessed with 2-deoxy-2-[ 18 F]fluoro- d -glucose ([ 18 F]FDG) and studied by using small-animal PET imaging. A total of 59% of the mice developed metastatic tumors. Micro-CT image analysis was able to identify and follow up to 36% of metastatic lesions. Examples of metastatic lesions identified and followed up by micro-CT imaging included a lung metastasis, mandibular metastasis, subcutaneous metastasis, and tibial/femoral metastasis. Micro-CT and small-animal PET fusion imaging successfully correlated anatomic localization of glucose metabolism of the metastatic tumors. Micro-CT and small-animal PET imaging were found to be highly effective in detection and characterization of lesions produced by this metastatic melanoma model.